International course of physical and sportive education (Fiep Bulletin - online, 2015)
This course that was held at the CREPS of houlgate (Normandy) under the international patronage of the FIEP has been another great achievement of the FFGEGV that is heiress of the ancient “Ligue Française d’éducation Physique” founded in 1888 by the eminent French scientist Dr. Philippe Tissié who, in remarkable works, still of the greatest interest, gave to body exercises a formative and hygienic of rational pedagogy.